A vision on biomass-to-liquids (BTL) thermochemical routes in integrated sugarcane biorefineries for biojet fuel production. (March 2020) - Neves, Renato Cruz; Klein, Bruno Colling; da Silva, Ricardo Justino; Rezende, Mylene Cristina Alves Ferreira; Funke, Axel; Olivarez-Gómez, Edgardo; Bonomi, Antonio; Maciel-Filho, Rubens
Abstract: Crude oil price volatility directly affects the worldwide fuels and chemicals markets, impacts food production costs, as well as it influences investments in alternative energy sources. Global warming is a consequence of greenhouse gases emissions, among which CO2 plays a crucial role. A circular economy appears to be a global consensus to limit the negative impacts on the environment caused by fossil-based emissions. Transportation of goods and people are responsible for a large fraction of manmade CO2 vented to the atmosphere. Although alternatives have already been developed and are already in use for Otto and Diesel cycle engines in the form of bioethanol and biodiesel, respectively, the aviation sector is still short of a consolidated solution for biojet fuel procurement. Among the possible pathways, Biomass-to-Liquids (BTL) thermochemical routes are candidates to produce green hydrocarbons in the near future, including biojet fuel. For the deployment of a BTL thermochemical route, a true biorefinery concept can be employed, through which a flexibility in the product portfolio may increase business competitiveness and reduce production costs through heat and mass integration. Bearing this context in mind, the present work presents a vision on BTL thermochemical routes focusing on biojet fuel production through fast pyrolysis, gasification, and Fischer-Tropsch (FT) synthesis in integrated sugarcane biorefineries. Graphical abstract: Image 1 Highlights: Biomass-to-Liquid route for biojet fuel production. Emphasis on fast pyrolysis, gasification and Fischer-Tropsch synthesis. Integration to a First Generation (1G) sugarcane biorefinery. Centralized and decentralized concepts.